2021
DOI: 10.1016/j.jpeds.2021.08.068
|View full text |Cite
|
Sign up to set email alerts
|

Screen Time in the Coronavirus 2019 Era: International Trends of Increasing Use Among 3- to 7-Year-Old Children

Abstract: Objective: To evaluate changes in electronic screen-based media use in 3-to 7-year-old children across six countries as a result of the COVID-19 pandemic.Study design: Between April and July 2020, parents of 2516 children completed online survey measures reporting current ("now") and retrospective ("before the pandemic") screen-based media use for the purposes of entertainment, educational app use, and socializing with family and friends. Parents also reported family socioeconomic characteristics and impacts o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 29 publications
4
33
0
Order By: Relevance
“…A recent large scale survey done in several countries reported a significant increase in screen time among preschool children globally during the pandemic [ 31 ]. Another survey carried out among children aged between 3–7 years from six countries revealed an average of 50-min increase in daily screen time during the pandemic, of which approximately 40 min accounted for entertainment [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent large scale survey done in several countries reported a significant increase in screen time among preschool children globally during the pandemic [ 31 ]. Another survey carried out among children aged between 3–7 years from six countries revealed an average of 50-min increase in daily screen time during the pandemic, of which approximately 40 min accounted for entertainment [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased use of electronic screen devices has become a significant health problem in the paediatric population worldwide [ 8 ]. Studies done in developed countries have shown a rapid increase in the rate of screen device usage among children over the past decade [ 9 , 10 ]. Similarly, the average age of using electronic screen devices has declined steadily [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regrettably, the spread of the novel coronavirus (COVID-19) since early 2020 further increased the risk of excessive screen use by children [ 6 ]. With school closures and lockdown policies implemented in many parts of the world at the beginning of the pandemic, children were confined at home with their parents, with few activities available other than using digital devices [ 7 – 11 ].…”
mentioning
confidence: 99%
“…The impact of the COVID-19 pandemic on increased screen time for all ages [ 61 ] is troubling given that screen time has been associated with obesity [ 62 ] and is a risk factor for severe obesity in children under 5 [ 63 ]. Children ages 3–7 across six countries reported increased screen time [ 64 ] and even children as young as 8–36 months are acquiring more screen time than before COVID-19 [ 65 ]. Future research should explore what providers know about why screen-time limits are recommended and to help develop training and tools to facilitate conversations between providers and parents about the importance of limiting screen time.…”
Section: Discussionmentioning
confidence: 99%